Exploring the impact of a KCNH2 missense variant on Long QT syndrome: insights into a novel gender-selective, incomplete penetrance inheritance mode - Chen, Peng; Zampawala, Zainul; Wang, Hong; Wang, Luyun (Frontiers in Genetics, 2024)
Background: Long QT syndrome (LQTS) is an inherited malignant arrhythmia syndrome that poses a risk of sudden death. Variants in the Potassium Voltage-Gated Channel Subfamily H Member 2 (KCNH2) gene are known to cause Long QT syndrome through an autosomal dominant inheritance pattern. However, as of now, there have been no reports of any KCNH2 variant leading to Long QT syndrome exhibiting incomplete penetrance that is influenced by gender.Methods: Whole-exome sequencing (WES) was conducted on the proband to identify pathogenic variants. Subsequently, Sanger sequencing was employed to validate the identified likely pathogenic variants in all family members.We analyzed a pedigree spanning three-generations afflicted by Long QT syndrome. WES revealed a novel KCNH2 missense variant (p.Val630Gly, c.1889 T>G) as the causative factor for the family's phenotype.Within this family, all three male carriers of the KCNH2 variant carriers exhibited the Long QT syndrome phenotype: one experienced sudden death during sleep, another received an implantable cardioverter-defibrillator (ICD), and a younger man displayed a prolonged QTc interval without any instances of syncope or malignant arrhythmia to date. Interestingly, the middle-aged female carrier showed no Long QT Syndrome phenotype. However, her offspring, diagnosed with Turner syndrome (45, X) and also a carrier of this variant, experienced frequent syncope starting at 12 years old and was diagnosed with Long QT syndrome, leading to an ICD implantation when she was 15 years old. These observations suggest that the manifestation of Long QT syndrome associated with this KCNH2 variant exhibits incomplete penetrance influenced by gender within this family, indicating potential protective mechanisms against the syndrome in females affected by this variant.Our investigation has led to the identification of a novel pathogenic KCNH2 variant responsible for Long QT syndrome within a familial context characterized by gender-selective, incomplete penetrance. This discovery highlights a unique pathogenic inheritance pattern for the KCNH2 gene associated with Long QT syndrome, and could potentially shed light on the distinct penetrance behaviors and patterns of the KCNH2 gene. This discovery broadens our exploration of the KCNH2 gene in cardiac arrhythmias, highlighting the intricate genetic dynamics behind Long QT syndrome.